Sistem Pendukung Keputusan Pemilihan Smartphone Menggunakan Metode SAW dan Personalisasi Bobot Kriteria - Teodardus Guido; Kristina; Kartono (INTEKSIS, 2025)
The large number of smartphone variations available on the market makes it difficult for users to determine the choice that best suits their needs and preferences. The approach used in the study is descriptive, with data collection methods through literature studies. The system design is visualized using the Unified Modeling Language (UML) and is planned to be implemented with PHP, HTML, JavaScript, CSS, and a MySQL database. The study aims to design a web-based decision support system (DSS) to select a smartphone using the Simple Additive Weighting (SAW) method. The criteria processed in the DSS that were built were 7 consist of namely price, brand, processor, RAM, internal memory capacity, battery life, and main camera resolution. The system developed has features like user registration, data management, user login, weight preference setting, alternative assessment, and recommendations for the best types of smartphones. The results of data processing were carried out on 10 smartphone brands whose market share in Indonesia in the period 2020 to 2025, so that the number of smartphone units processed could be 100 smartphone units. The developed SPK can provide accurate recommendations and make it easier for users to choose a smartphone that suits their needs and preferences.